A decomposition method for finding solitary and periodic solutions for a coupled higher-dimensional Burgers equations - Kaya, D; Yokus, A (Elsevier Science Inc, 2005)
In this paper, we consider coupled higher-dimensional Burgers (chdBur) equations. We find periodic solutions to chdBur equations using a modified Adomian's decomposition method (mADM). We find both exact and numerical solutions. We compared the numerical solutions with corresponding analytical solutions. We also show the effectiveness of the method. (c) 2004 Elsevier Inc. All rights reserved.
Keywords: coupled higher-dimensional Burgers equations; modified Adomian decomposition method; exact periodic solutions; numerical solutions